2019
DOI: 10.4049/jimmunol.1700950
|View full text |Cite
|
Sign up to set email alerts
|

The Activation State of CD4 T Cells Alters Cellular Peptidase Activities, HIV Antigen Processing, and MHC Class I Presentation in a Sequence-Dependent Manner

Abstract: CD4 T cell activation is critical to the initiation of adaptive immunity. CD4 T cells are also the main targets of HIV infection, and their activation status contributes to the maintenance and outcome of infection. Although the role of activation in the differentiation and proliferation of CD4 T cells is well studied, its impact on the processing and MHC class I (MHC-I) presentation of epitopes and immune recognition by CD8 T cells are not investigated. In this study, we show that the expression and hydrolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 65 publications
(121 reference statements)
3
18
0
Order By: Relevance
“…In contrast PKCa significantly increased aminopeptidase and proteasomal activities (2.05-to 4.9-fold increase depending on the activities) but to a lesser extent than TCR activation. Our previous work indicated that the increase in peptidase activities following aCD3/CD28-stimulation is positively correlated with cellular activation of primary CD4 T cells [37]. We assessed the expression of activation markers CD25 and CD69 at the surface of primary CD4 T cells following LRA-treatment ( Fig 1D).…”
Section: Different Classes Of Lra Alter Cytosolic Peptidase Activitiesmentioning
confidence: 95%
See 4 more Smart Citations
“…In contrast PKCa significantly increased aminopeptidase and proteasomal activities (2.05-to 4.9-fold increase depending on the activities) but to a lesser extent than TCR activation. Our previous work indicated that the increase in peptidase activities following aCD3/CD28-stimulation is positively correlated with cellular activation of primary CD4 T cells [37]. We assessed the expression of activation markers CD25 and CD69 at the surface of primary CD4 T cells following LRA-treatment ( Fig 1D).…”
Section: Different Classes Of Lra Alter Cytosolic Peptidase Activitiesmentioning
confidence: 95%
“…We measured with a fluorescence-based enzymatic assay the hydrolytic activities of the proteasome (chymotryptic, tryptic-like and caspase-like activities) and the post-proteasomal aminopeptidase activities involved in MHC-I presentation in live CD4 T cells of healthy donors at 6, 24 and 48 hours post-treatment [37] (Fig 1). Peptidase activities significantly changed after a 48 hours treatment ( Fig 1A).…”
Section: Different Classes Of Lra Alter Cytosolic Peptidase Activitiesmentioning
confidence: 99%
See 3 more Smart Citations